ANALISIS PERAN KAPABILITAS INOVASI DAN KEUNGGULAN DIFERENSIASI DALAM MENINGKATKAN KINERJA UMKM BERBASIS ORIENTASI KEWIRAUSAHAAN DI PULAU JAWA - Angela Steffi Haryono; Patricia; Natalia Chris Dayanti (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
This research investigates the mediating role of innovation capability and the direct influence of differentiation advantage on the performance of Small and Medium Enterprises (SMEs) based on entrepreneurial orientation in Java Island. This study employs a quantitative approach with a sample of 235 SME owners from various busines sectors. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS software to test structural relationships between variables. The results show that entrepreneurial orientation has a positive effect on innovation capability and differentiation advantage, but no direct effect on business performance. Conversely, innovation capability and differentiation advantage have a positive effect on business performance. Furthermore, innovation capability and differentiation advantage serve as significant mediators in the relationship between entrepreneurial orientation and business performance. These findings indicate that entrepreneurial orientation needs to be transformed through innovation capability and differentiation strategy to influence business performance, as the effect is not automatic. This research provides theoretical contributions by integrating the Resource-Based View and Dynamic Capability Theory perspectives in explaining the relationship mechanism between EO and performance. Practically, the results emphasize the importance of developing innovation capability and differentiation as primary strategies for improving SME performance in a competitive business environment.